1995
DOI: 10.1163/156856294x00590
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation and release of glucose oxidase and interleukin 2 from a bead formed macroporous hydrophilic polymer matrix

Abstract: Freeze-thaw photopolymerization at low temperature of a mixed solution of 2-hydroxyethyl methacrylate (HEMA), ethylene glycol dimethacrylate (EDM), and either glucose oxidase (GOx) or interleukin 2 (IL-2) around frozen ice crystals has been used to generate a bead-formed macroporous hydrophilic matrix with potential for immobilization and sustained release. The mean equilibrium acetate buffer content (EBC) of unloaded p-HEMA beads at room temperature and controlled humidity was ≈72%. The incorporation of GOx i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It was shown that severe toxicity can be induced by the prolonged high doses of systemic IL-2 (28). Previous attempts on localized IL-2 delivery include the use of dextran gels (29), liposomes (30,31), PLGA microspheres (32,33), and HEMA films (34). These studies showed that VEGF and IL-2 can be released for a 1-to 3-week period, but these delivery methods suffered from the rapid initial burst release, low total fraction released, nonlinear release, and rapid protein denaturation within the first week of release.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that severe toxicity can be induced by the prolonged high doses of systemic IL-2 (28). Previous attempts on localized IL-2 delivery include the use of dextran gels (29), liposomes (30,31), PLGA microspheres (32,33), and HEMA films (34). These studies showed that VEGF and IL-2 can be released for a 1-to 3-week period, but these delivery methods suffered from the rapid initial burst release, low total fraction released, nonlinear release, and rapid protein denaturation within the first week of release.…”
Section: Introductionmentioning
confidence: 99%
“…Several delivery systems for IL‐2 have been used, both liposomal formulations and polymer‐based release systems7–17 (for review, see ref. 18), but control over the release rate of IL‐2 has been difficult to achieve.…”
mentioning
confidence: 99%